Increased risk of herpes zoster with tofacitinib treatment in Korean patients with rheumatoid arthritis: a single-center prospective study - Song, Yeo-Jin; Cho, Soo-Kyung; Kim, Hyoungyoung; Kim, Hye Won; Nam, Eunwoo; Jeon, Ja-Young; Yoo, Hyun-Jeong; Choi, Chan-Bum; Kim, Tae-Hwan; Jun, Jae-Bum; Bae, Sang-Cheol; Yoo, Dae Hyun; et al. (Scientific reports, 2023)
We aimed to determine the risk of herpes zoster (HZ) in Korean rheumatoid arthritis (RA) patients on tofacitinib compared with tumor necrosis factor inhibitor (TNFi) treatment. From the prospective cohorts of RA patients who started tofacitinib or TNFi in an academic referral hospital in Korea, patients who started tofacitinib between March 2017 and May 2021 and those who started TNFi between July 2011 and May 2021 were included. Baseline characteristics of tofacitinib and TNFi users were balanced through inverse probability of treatment weighting (IPTW) using the propensity score including age, disease activity of RA and medication use. The incidence rate of HZ in each group and incidence rate ratio (IRR) were calculated. A total of 912 patients were included: 200 tofacitinib and 712 TNFi users. There were 20 cases of HZ among tofacitinib users and 36 among TNFi users during observation period of 331.4 person-years (PYs) and 1950.7 PYs, respectively. In IPTW analysis with a balanced sample, IRR of HZ was 8.33 (95% confidence interval 3.05–22.76). Tofacitinib use increased the risk of HZ compared with TNFi in Korean patients with RA, but the rate of serious HZ or permanent discontinuation of tofacitinib due to HZ event was low.